Calcitonin as an adjunct for phantom limb pain - Sneha Vidyasagar; Kanakamani Jeyaraman; Syeda Farah Zahir; Paul Varghese (PLoS ONE, 2026)
Objective This retrospective study evaluated calcitonin as an adjunct therapy for reducing phantom limb pain (PLP) following lower limb amputation. Method The study included 35 patients who received at least 3 days of calcitonin treatment between January 1, 2017, and December 31, 2023. We collected demographic data and pain ratings (intensity, distress, and interference with activity) before and after calcitonin treatment. Descriptive statistics and paired t-tests analysed the data, with a two-way repeated measures ANOVA used to compare outcomes between patients with and without diabetes. Raw and Standardized mean differences (Cohen’s d) are presented for each measure. Results The average age of participants was 57.09 years (SD = 13.66), with 40% female. Amputation types were below-knee (65.7%), above-knee (25.7%), and other (8.6%). The main causes of amputation included diabetic foot infection (25.7%), peripheral vascular disease (34.3%), trauma (25.7%), and other (14.3%). Ten participants had diabetes, and 20% had depression. Calcitonin was associated with significant reductions in pain outcomes from pre- to post-intervention (Day 0 to Day 7), with calcitonin given from day 1–3. Mean pain intensity decreased from 6.41 to 5.24 (Cohen’s d = 0.66); p = 0.02), and pain-related distress decreased from 5.85 to 4.81 (Cohen’s d = 0.71; p = 0.014). Perceived pain relief scores increased from 33.69 to 58.21, indicating greater patient-reported pain relief following treatment (Cohen’s d = 0.53; p = 0.035). No significant differences in pain intensity or distress were observed between patients with and without diabetes. Additionally, there was no significant change in the Oral Morphine Equivalent Daily Dose (p = 0.94). Conclusion In conclusion, calcitonin significantly reduced perceived pain intensity and pain-related distress scores while increasing perceived pain relief scores (i.e., patients’ reported degree of pain reduction), with similar effects observed in both patients with and without diabetes.